Gynaecology illustrated - Bain, Catrina (Churchill Livingstone/Elsevier, 2011)
A visual presentation of Gynaecology suitable for undergraduate medical students. It covers concise text and associated diagrams. Its visual presentation of information is effective for examination preparations.